The Role of Internal Communication and Employee Engagement in The Performance of Medical Workers at Klinik Ismail Medika - Kusumah, Ismail; Supriyadi, Supriyadi; Zaharuddin, Zaharuddin (IJBLE Scientific Publications Community Inc., 2025)
Internal communication and employee engagement are crucial factors in improving the performance of medical workers, especially in clinical environments that demand efficiency, coordination, and high-quality services. This study aims to analyze the role of internal communication and employee engagement in the performance of medical workers at Klinik Ismail Medika. The research method used is a quantitative approach with a survey technique conducted among medical personnel in the clinic. Data were collected through questionnaires measuring the effectiveness of internal communication, employee engagement levels, and medical staff performance. The study results indicate that effective internal communication positively contributes to increasing employee engagement, which ultimately impacts the performance of medical workers. The implications of this study emphasize that clinic management needs to develop more effective internal communication strategies and create a work culture that supports employee engagement to enhance the quality of healthcare services.